Agrotechnical Measures for Growing Onion Tuli Netherlands in Climatic Conditions of Namangan Region (Eurasian Scientific Herald, 2023)
This article is devoted to research on the growth, development and productivity of 10 local species in 2018 and 16 rounds in 2019 introduced from the Netherlands tulip varieties. Research material - locally planted bulbs of local varieties amounted to 4500 units per hectare in 2018, 22500 introduced varieties in 2019. Before planting the bulbs, refrigeration technology was applied at a temperature of 4-5 ° C for 16 weeks. The main the objective of this study is to identify fertile onion varieties that are resistant to all climatic conditions and various diseases and by comparing local and introduced varieties to determine the most optimal options.